Changes in T Cell and Dendritic Cell Phenotype from Mid to Late Pregnancy Are Indicative of a Shift from Immune Tolerance to Immune Activation - Shah, Nishel Mohan; Herasimtschuk, Anna A.; Boasso, Adriano; Benlahrech, Adel; Fuchs, Dietmar; Imami, Nesrina; Johnson, Mark R. (Frontiers in Immunology, 2017)
During pregnancy, the mother allows the immunologically distinct feto-placental unit to develop and grow. Opinions are divided as to whether this represents a state of fetal specific tolerance or of a generalised suppression of the maternal immune system. We hypothesised that antigen-specific T cell responses are modulated by an inhibitory T cell phenotype and modified dendritic cell (DC) phenotype in a gestation dependent manner. We analysed changes in surface markers of peripheral blood T cells, ex vivo antigen specific T cell responses, indoleamine 2,3-dioxygenase (IDO) activity (kynurenine/tryptophan ratio KTR), plasma neopterin concentration and the in vitro expression of progesterone-induced blocking factor (PIBF) in response to PBMC cell culture with progesterone. We found that mid gestation is characterised by reduced antigen-specific T cell responses associated with 1) predominance of effector memory over other T cell subsets; 2) up-regulation of inhibitory markers (PD-L1); 3) heightened response to progesterone (PIBF); and 4) reduced proportions of myeloid DC and concurrent IDO activity (KTR). Conversely antigen specific T cell responses normalised in late pregnancy and were associated with increased markers of T cell activation (CD38, neopterin). However these changes occur with a simultaneous up-regulation of immune suppressive mechanisms including apoptosis (CD95), co-inhibition (TIM-3) and immune regulation (IL-10) through the course of pregnancy. Together, our data suggest that immune suppression dominates in the second trimester and that it is gradually reversed in the third trimester in association with immune activation as the end of pregnancy approaches.